An Introduction to the Open Data User Group (Journal of Open Law, Technology & Society, 2015)
This article gives a succinct introduction to the work of the Open Data User Group and the impact of demand driven open data on the UK economy, society and political landscape. It highlights the global importance of Transparency to societies and how the UK is at the forefront of this growing movement. It ends with a look into the future and how Open Data could impact the lives of citizens and the activities of businesses.